2017
DOI: 10.1136/heartjnl-2016-309981
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary exercise testing for detecting pulmonary arterial hypertension in systemic sclerosis

Abstract: CPET is a safe and valuable method in the non-invasive detection of SSc-associated PAH. It may be particularly beneficial for reducing unnecessary RHC procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 24 publications
(27 reference statements)
2
53
0
11
Order By: Relevance
“…Very recently, Dumitrescu et al demonstrated in patients with systemic sclerosis that peak VO 2 and VE/VCO 2 had a high correlation with PAP, TPG and PVR.…”
Section: Discussionmentioning
confidence: 98%
“…Very recently, Dumitrescu et al demonstrated in patients with systemic sclerosis that peak VO 2 and VE/VCO 2 had a high correlation with PAP, TPG and PVR.…”
Section: Discussionmentioning
confidence: 98%
“…Reddy et al 31 demonstrated that, in the differentiation of HFpEF from patients with noncardiac dyspnea, there was significant overlap in peak O 2 consumption alone without invasive measures (Figure 1). nCPET may be useful diagnostically, however, only when targeted to specific at-risk populations such as scleroderma patients 32 or those in whom PH is suspected by echocardiograpy. 33 Data from nCPET incrementally predicts mortality when added to resting hemodynamics.…”
Section: Methodsmentioning
confidence: 99%
“…Eine Hypoxämie in Ruhe kann unter Belastung zunehmen, insbesondere bei Auftreten eines Rechts-Links-Shunts bei steigendem rechtsatrialem Druck und offenem Foramen ovale [189,191]. Diese charakteristischen Befundmuster können bei einem Teil symptomatischer Sklerodermiepatienten auch mit unauffälligen echokardiografischen Befunden gesehen werden [192], sodass spiroergometrische Parameter der Leistungsfähigkeit (peak V O 2 ) und der Atemeffizienz (Nadir V E/V CO 2 ) relevante Aussagen zur Abschätzung der Wahrscheinlichkeit einer PAH bei symptomatischen Sklerodermiepatienten treffen können [193].…”
Section: Neue Parameter Der Spiroergometrieunclassified